Using distributed consistent branching for efficient reconciliation of mobile workspaces - Hupfeld, F.; Gordon, M. (2006 International Conference on Collaborative Computing : Networking, Applications, and Worksharing : 17-20 November 2006 : Atlanta, GA, 2006)
Optimistic replication allows mobile workspaces to remain accessible during interrupted network access, but require consecutive handling of any conflicts. When conflict handling requires manual intervention by the user, the system must not require that conflicts are resolved immediately after their detection. We present a log-based algorithm for reconciling changes to replicated data that supports deferred manual conflict resolution, while sharing the favorable scalability properties of log-based approaches of small storage and communication overhead. Simulation results validate our design and show that it compares favorably in the relevant metrics with version vector-based designs